Answer:
If the expression is
, then the answer is the first option.
If the expression is
, then the answer is the third option.
Step-by-step explanation:
Remember that when you have a radical expression in the form
, you can rewrite as:
![=x^\frac{1}{n}](https://tex.z-dn.net/?f=%3Dx%5E%5Cfrac%7B1%7D%7Bn%7D)
Then:
- If the expression is
, then you can rewrite it in the following radical form:
(This form matches with the first option.)
- If the expression is
, then you can rewrite it in the following radical form:
(This form matches with the third option).
(y-x) (2+3)= (yx)(5)
But am not sure it could be =(2-3) (y+x) = (1) (yx)
Answer:
-3
Step-by-step explanation:
When you have an equation in the form y=mx+b, then the number at the end is the y-intercept.